Antidiabetic and antihyperlipidemic activities of Forsythia suspensa (Thunb.) Vahl (fruit) in streptozotocin-induced diabetes mice. (4th November 2016) - Zhang, Yanyan; Feng, Fu; Chen, Ting; Li, Zhongwen; Shen, Qingwu W.
Abstract: Ethnopharmacological relevance: The fruit of Forsythia suspense (Thunb.) Vahl, a well-known Chinese Materia Medica, has been traditionally used in traditional Chinese medicine for the treatment of diabetes and some other diseases, but the rational for the usage of this plant is unclear. The aim of this study was to investigate the therapeutic effect and potential mechanism of the fruit of F. suspensa using streptozotocin (STZ)-induced diabetic mice. Materials and methods: Crude methanol extract of F. suspense fruit was fractionated with different solvents and the ethyl acetate fraction (EAF) was selected for in vivo studies based on the in vitro α-amylase and HMG-CoA reductase (3-hydroxy-3-methyl-glutaryl coenzyme A) inhibiting activities. For in vivo study, diabetes mellitus was induced in mice with STZ. Diabetic mice were orally administrated with 50, 100 and 200 mg/kg body weight of EAF for 4 weeks. Mouse body weight, blood glucose, glucose tolerance, biochemical parameters and gene expression related to pancreas and liver function were analyzed after EAF administration. Results: After 4 weeks of EAF intervention, a significant decrease in blood glucose, triglyceride, creatinine total cholesterol, acid phosphatase, alkaline phosphatase, aspartate transaminase, alanine transaminase, and hepatic lipid (triglycerides and cholesterol) content as well as a significant increase in body weight, insulin secretion and glucose tolerance was observed in EAF treated diabetic mice. qRT-PCR analysis revealed that EAF antagonized STZ-induced alteration of the expression of rate-limiting enzymes (glucokinase and phosphorenolpyruvate carboxykinase) in liver and insulin secretion related genes insulin-1, insulin-2 and duodenal homeobox factor-1 in pancreas. Conclusion: The ethyl acetate extract of Forsythia suspense (Thunb.) Vahl fruit has potency to develop an antihyperglycemic and antihyperlipidemic agent for the treatment of diabetes mellitus via modulation of oxidative stress, the hepatic glucose metabolism and pancreatic insulin secretion. Graphical abstract: